The Potential for Early Health Economic Modelling in Health Technology Assessment and Reimbursement Decision-Making; Comment on "Problems and Promises of Health Technologies: The Role of Early Health Economic Modeling" - Hansoo Kim; Stephen Goodall; Danny Liew (Kerman University of Medical Sciences, 2021)
Grutters et al recently investigated the role of early health economic modelling of health technologies by undertaking a secondary analysis of health economic modelling assessments performed by their group. Our commentary offers a broad perspective on the potential utility of early health economic modelling to inform health technology assessment (HTA) and decision-making around reimbursement of new health technologies. Further we provide several examples to compliment Grutters and colleagues' observations.